Doing ethics : An outline of a constructivist and phenomenological approach of moral communication - Drescher, Martina; Institute of African Studies (Institute of African Studies, 2024)
Situated at the crossroads of pragmatics and interactional linguistics, the aim of the present working paper is to sketch a theoretical framework that is able to capture the linguistic and communicative facets of everyday moralities. Based on a phenomenological, constructivist and dynamic understanding which is informed by recent sociological and anthropological research, the case is made that moralities are best conceptualized as an interactional achievement, in other words, as ‘doing ethics’. Moreover, it is argued that communication plays a major role in doing ethics. Hence, moralities are explored in relation with language. The focus is on everyday moral communication and, in particular, on the verbal means and communicative practices conventionally used to signal moral meanings. The main purpose is to flesh out a conceptualization of doing ethics which opens up this domain for pragmatic and interactional approaches. Thus, theoretical considerations are prevalent in the working paper.
Keywords: Ethics: moral; Moralities; linguistics; Communication; pragmatics; interactional linguistics; phenomenology; constructivism